Models of Community-Based Coastal Area Management in Galesong District - Hasriyanti; Faisal, Siti Raihanah Rinduputri; Reskiyanti; Syukur, Abd Rahmad (Jurnal Multidisiplin Madani, 2024)
Abrasion that continues to threaten the lives and livelihoods of local communities due to tidal waves causes the coastline in North Galesong Subdistrict to continue to regress. Structural and non-structural mitigation efforts need to be carried out to avoid material losses and casualties, as well as potential disasters that will occur. Starting from reducing abrasion, breaking waves, understanding sedimentation, making disaster paths and evacuation, regulating policies, to local wisdom in the lives of coastal communities, maximum efforts need to be made as a systemic step in reducing disaster threats. Among the steps that can be taken, there is an important role owned by the local wisdom of the community, namely so that the coastal environment can be preserved through a business. Communities located in disaster-prone locations require approaches and mechanisms for them which are carried out with mechanisms that apply in the community on an ongoing basis. Traditions that are in people's lives ranging from taboos, prohibitions, and other taboos in environmental and natural preservation provide considerable meaning and messages